Intraocular lens tilt and decentration: A concern for contemporary IOL designs - Ale, Jit B (Nepalese Journal of Ophthalmology, 2011)
Purpose: To review published studies reporting the posterior chamber intraocular lens tilt and decentration after surgically uneventful implantation. Potential influences of normally occurring misalignment of modern designs of IOL on the optical performances are discussed. Materials and methods: Published theoretical and clinical studies in relation to primarily implanted posterior chamber intraocular lenses and reports relating to more recent development of intraocular lens technologies were reviewed. Results: Capsulotomy type and integrity, ocular pathology, fixation position of the haptics are some of the important factors causing the misalignment. On an average, a 2-3 degrees tilt and a 0.2 -0.3 mm decentration are common, and which remain clinically unnoticed for any design of IOL. However, theoretical studies predict deterioration of retinal image quality particularly with customized wavefront correcting IOLs. More than a 10 degrees tilt and above 1 mm decentration are occasionally reported even with modern cataract surgery in about 10 % of pseudophakic population. Conclusions: The rate and extent of the complication have lowered substantially concomitant with developments in surgical techniques and IOL designs. While emerging designs of modern IOLs offer improved quality of postoperative vision, optimum performance is vastly influenced by the position of the device in the eye. Therefore, additional precision in alignment of modern designs of IOL may be warranted. Key words: IOL misalignment; Intraocular Lens; modern IOL; consequences of misalignment DOI: 10.3126/nepjoph.v3i1.4281 Nepal J Ophthalmol 2011;3(5):68-77